The Implementation of Sustainability Audit: Challenges and Opportunities in the Digital Era - Sumartono (Universitas Yapis Papua, 2023)
As the global business landscape continues to grapple with the pressing need for sustainable practices, sustainability audits have emerged as a crucial tool to assess and enhance environmental, social, and economic performance. With the advent of the digital era, the implementation of sustainability audits has seen both significant challenges and promising opportunities. This literature review critically examines the state of sustainability audit implementation in the context of the digital era, shedding light on the key hurdles and prospects. The literature review begins by providing a comprehensive overview of sustainability audits, emphasizing their role in promoting transparency, accountability, and responsible business conduct. It explores the evolving global sustainability reporting standards and regulations, such as the Global Reporting Initiative (GRI) and the Sustainability Accounting Standards Board (SASB), which have catalyzed the uptake of sustainability audits. The digital era has revolutionized data collection, analysis, and reporting, offering sustainability auditors powerful tools to process vast amounts of information efficiently. Opportunities arising from this digital transformation include the use of big data analytics, artificial intelligence, and blockchain technology for more accurate and real-time sustainability reporting. These technologies can help companies identify environmental and social risks, track progress, and respond to stakeholder demands with agility. However, the review also highlights significant challenges in the implementation of sustainability audits in the digital era. These challenges include data privacy concerns, data security risks, and the digital divide, which may limit access to digital tools for small and medium-sized enterprises (SMEs). Additionally, the quality and reliability of sustainability data remain areas of concern, as they can be affected by greenwashing and inaccurate reporting. In conclusion, the digital era has provided both challenges and opportunities for the implementation of sustainability audits. As businesses strive to align their operations with sustainability goals, the digital tools at their disposal can be harnessed to improve sustainability audit processes and overall sustainability performance. This literature review contributes to a deeper understanding of the complexities of sustainability audit implementation in the digital era, helping guide future research and practical applications in this dynamic field.